Estimating methane emissions from biological and fossil‐fuel sources in the San Francisco Bay Area. Issue 1 (9th January 2017) - Jeong, Seongeun; Cui, Xinguang; Blake, Donald R.; Miller, Ben; Montzka, Stephen A.; Andrews, Arlyn; Guha, Abhinav; Martien, Philip; Bambha, Ray P.; LaFranchi, Brian; Michelsen, Hope A.; Clements, Craig B.; et al.
Abstract: We present the first sector‐specific analysis of methane (CH4 ) emissions from the San Francisco Bay Area (SFBA) using CH4 and volatile organic compound (VOC) measurements from six sites during September – December 2015. We apply a hierarchical Bayesian inversion to separate the biological from fossil‐fuel (natural gas and petroleum) sources using the measurements of CH4 and selected VOCs, a source‐specific 1 km CH4 emission model, and an atmospheric transport model. We estimate that SFBA CH4 emissions are 166–289 Gg CH4 /yr (at 95% confidence), 1.3–2.3 times higher than a recent inventory with much of the underestimation from landfill. Including the VOCs, 82 ± 27% of total posterior median CH4 emissions are biological and 17 ± 3% fossil fuel, where landfill and natural gas dominate the biological and fossil‐fuel CH4 of prior emissions, respectively. Key Points: Methane and VOCs are used for source apportionment of methane emissions SFBA methane emissions are 1.3‐2.3 times a recent inventory Biological source emissions are higher than fossil‐fuel emissions